Non-electrophilic TRPA1 agonists, menthol, carvacrol and clotrimazole, open epithelial tight junctions via TRPA1 activation. (19th May 2020) - Mukaiyama, Minagi; Usui, Takeo; Nagumo, Yoko
Abstract: Activation of the transient receptor potential A1 channel (TRPA1) by electrophilic agonists was reported to induce the opening of tight junctions (TJs). Because compounds that increase TJ permeability can be paracellular permeability enhancers, we investigated the effect of non-electrophilic TRPA1 activators, including food ingredients (menthol and carvacrol) and medication (clotrimazole), on epithelial permeability. We show that all three compounds induced increase of the permeability of fluorescein isothiocyanate-conjugated dextran (4 kDa) and decrease of transepithelial electrical resistance, accompanied by Ca 2+ influx and cofilin activation in epithelial MDCK II monolayers. These phenotypes were attenuated by pretreatment of a TRPA1 antagonist, suggesting TRPA1-mediated opening of TJs. These results suggest that non-electrophilic TRPA1 activators with established safety can be utilized to regulate epithelial barriers.